Attaining interprofessional competencies through a student interprofessional fellowship program. Issue 3 (May 2015) - Blue, Amy; Mitcham, Maralynne; Koutalos, Yiannis; Howell, David; Leaphart, Amy
Abstract For students interested in enriching their interprofessional competencies beyond those required and offered by their academic programs, an elective interprofessional education fellowship can serve that need. We designed a fellowship for students linking a conceptual framework grounded in adult learning principles. During the fellowship, students progress through three levels of learning as they acquire, apply, and demonstrate interprofessional collaborative knowledge and skills; fellowship activities are self-directed. A content analysis of students' fellowship summary reports sought to determine the effectiveness of the fellowship as a learning experience to acquire interprofessional collaborative competences. Results indicated that students most consistently report competencies associated with acquisition of values and ethics for interprofessional practice, roles/responsibilities, and teams/teamwork; interprofessional communication was implied. All students expressed commitment to interprofessional collaborative behavior when in practice. Based on the results from this study, this fellowship structure may serve as a model for other institutions to adapt and implement for best practice and best fit.